Evaluation of Processed Cassava Peel Meals as Substitutes for Maize in the Diets of Layers - Salami, R.I.; Odunsi, A.A. (International Journal of Poultry Science, 2003)
The response of Isa Brown layers during 56 to 72 weeks of age to cassava peel meal (CPM) processed by different methods i.e. ensiling (ECPM), parboiling (PCPM), retting (RCPM) and sun-drying alone (SCPM) as substitutes for maize was investigated. The control diet (CD) contained 40% maize and each of ECPM, PCPM, RCPM and SCPM were used to substitute 50, 75 and 100% of the maize in the CD. Dietary protein ranged from 15-16% while metabolizable energy varied between 2,500 and 2,600 Kcal/kg. Performance in terms of hen-day production and egg weight showed that RCPM could satisfactorily replace up to 75% of maize while the other processed CPMs could not replace maize beyond 50% without jeopardizing these two parameters. The terminal body weights of layers fed 100%RCPM and PCPM at the expense of maize were not affected while ECPM and SCPM beyond 50% substitution level adversely affected body weight. Feed conversion ratio showed a slight improvement with the use of CPM, however, layers on 100%ECPM, 100%PCPM and those on SCPM had a worsened feed conversion compared with the CD. Feed cost per egg produced were better with layers fed processed CPM with the exception of those on sun dried peels. Comparatively, sun drying alone was inadequate for processing cassava peels while retting maintained terminal weight, and had higher savings in terms of feed cost per egg produced.